(.Effect of irrigated iron spray on green leaf and dry seeds for five varieties of the broad bean(Vicia faba L - Hammad, Hamid Saleh; Aziz, Emad Khalaf; Al Hayali, Arwa Ahmed Ibrahim (Journal of agricultural, environmental and veterinary sciences, 2018)
experimental field experience during the agricultural season 2016 to study the estimation of genetic parameters for varieties of the faba bean Under the influence of irrigated iron spry and the study included two factors ; The first is irrigated iron (13% iron W / W) and Add on three levels of 0 g. l-1 , 1 g. l-1 , 2 g. l-1 , and the second factor is five varieties of the faba bean and its Lortolano, Aquadulce, Luz de otono, Superaguadulce and the local class Hawija , And the study included 15 treatments , The results were statistically analyzed in split plot system within the design of complete random sector (R. C. B. D. (and three replicates and the results were compared using the Dunkin multidisciplinary test at a potential of 0. 05. The plants treated with the high concentration of 2 g. l-1 were superior in giving the highest values ​​in the number of horns in the plant, the green horns in the plant, the total number of green horns, the dry seed yield in the plant and the weight of 100 dry seeds , and 44. 05 pods. , 33. 87 tons. Hectar -1, 243. 05 g. Plants -1 and 190. 25 g, respectively, compared with non-irrigated irrigated with 22. 48 pods. Plant-1, 412. 8 g. Plants -1, 30. 65 tons. Hectare-1, 167. 73 g. Plant-1, 127. 45 g , respectively. There was no significant effect of the irradiation on the percentage of protein, carbohydrate and phosphorus in dry seeds.The cultivars differed significantly in most of the studied traits. Aquadulce was superior in the traits of one plant of the green pods and the total green mass (Tn. h-1)
Keywords: fermented iron; beans; varieties; qualities of growth